Enhancing fluency and accuracy in speaking through oral activities in VoiceThread (2016)
This paper describes an action research project that was conducted at Montessori School in Cartagena, Colombia. The study aims to influence students` fluency and accuracy in speaking through the implementation of some oral activities with VoiceThread; moreover, to describe how it contributes to the enhancement in terms of vocabulary, pronunciation and grammar and how it promotes the development of coherent and fluent ideas in speaking. VoiceThread is a web-based platform that enables teachers and students to create and share dynamic conversations around documents, pictures, diagrams and videos through a mix of media. The project involves the development of nine tasks over the pedagogical intervention in English, in which students are asked to record their participations in VoiceThread. The project describes in details the process in which the oral activities with VoiceThread improve students’ fluency and accuracy; and shows the progress achieved by students who reported difficulties in their speaking skills and who recorded all the proposed tasks. So, it is presented a brief analysis of the videos, surveys, and audios produced by these students before, during and after implementing the tasks in Voice Thread. Findings from this analysis suggest a significant improvement in spoken language and interaction after using technology tools. It is proved that speaking is an essential tool for communicating and technology is available for enhancing any language skill when used wisely. For this reason, it is emphasized the importance of including this type of innovative tasks and the use of technology in the classroom to promote opportunities for oral practice in all possible contexts and strengthen students´ confidence and motivation in speaking.